2016
DOI: 10.1519/jpt.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

High-Velocity Quadriceps Exercises Compared to Slow-Velocity Quadriceps Exercises Following Total Knee Arthroplasty: A Randomized Clinical Study

Abstract: HV quadriceps exercises may be an effective rehabilitation strategy in conjunction with a standardized progressive resistance exercise program beginning 4 to 6 weeks after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Therefore, it is important to improve gait function within the first few weeks after surgery. Various intervention methods focusing on the quadriceps, such as neuromuscular electrical stimulation7 ) and high-velocity training12 ) , were examined, and improvement in gait function was recognized. These interventions are thought to be based on the premise that the relationship between gait function and quadriceps strength is strong.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to improve gait function within the first few weeks after surgery. Various intervention methods focusing on the quadriceps, such as neuromuscular electrical stimulation7 ) and high-velocity training12 ) , were examined, and improvement in gait function was recognized. These interventions are thought to be based on the premise that the relationship between gait function and quadriceps strength is strong.…”
Section: Introductionmentioning
confidence: 99%
“…There were 64 (57%) studies that had mentioned exercise adherence within their study [ 18 , 19 , 22 ā€“ 24 , 27 , 29 , 31 , 33 , 34 , 36 ā€“ 38 , 42 ā€“ 47 , 50 , 53 , 54 , 58 , 59 , 63 , 65 ā€“ 69 , 73 , 74 , 78 , 79 , 82 ā€“ 84 , 86 , 90 ā€“ 93 , 96 ā€“ 100 , 102 ā€“ 104 , 107 ā€“ 109 , 111 , 112 , 114 , 117 , 118 , 121 , 123 , 126 , 127 , 129 , 131 ]. Of these studies only 41 (65%) reported sufficient information (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…There is initial evidence to support this paradigm in a small randomized controlled trial which found high velocity quadriceps exercise resulted in improved six-minute walk test performance compared to slow velocity exercise in patients after TKA. 22 Additionally, eccentric exercise effectively improved lower extremity rate of torque development in young and older adults. 23 This prior evidence and the inclusion of quadriceps rate of torque development in both regression models suggest that maximizing improvement in rate of torque development as a means of improving gait following TKA may be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%